Mössbauer Investigation on the Formation of Fe-containing Minerals in Coal during Gasification - F. B. Waanders (International Mineral Processing Congress, 2014)
Coal, as energy resource, possesses numerous characteristics and properties which all have an influence on its gasification behaviour. The two properties considered as critically important when evaluating a coal source for gasification is its mineral content and slagging behaviour. Research has indicated that slagging formation can be inhibited or even prevented by the addition of a fluxing agent. It is thus of great importance to understand the mineral interaction during gasification in order to select a suitable fluxing agent for the prevention of slagging and clinker formation in the gasifier. The aim of the present project is to evaluate the effect of iron as a fluxing agent and study the transformation of the mineral and added iron during gasification. A pre-determined amount of pure elemental iron (between 2wt% and 20wt%) was added to a base case coal sample in order to study the effect of the addition of iron to the coal. The transformation of the iron in conjunction with the possible iron containing minerals present in the coal was studied by means of Mössbauer analyses. Typical characterisation techniques included proximate analyses, ultimate analyses and ash composition analyses. The ash fusion temperature analyses (AFT) were used to study and predict the slagging behaviour of the iron-spiked coal samples. Even though AFT analyses only provide an average flow property, it gives a good indication of the changes that the iron addition induces on coal properties. FactSage modelling was carried out in conjunction with the Mössbauer and AFT analyses. From the proximate, ultimate and ash composition analyses it was clear that the coal used con-formed to the average characteristics measured over an extended time period. From the AFT values it was seen that an increase in the flow temperature occurred with the addition of pure elemental iron to the coal, which can be of importance for operational purposes as to raise the gasifier temperature and not to have slagging problems to occur in the gasifier. The Mössbauer data show that he-matite is the main Fe-component that forms from the pyrite originally present and from the added iron to the coal, consistent with FactSage modelling, which shows that the partial oxygen pressure determines which mineral species will form. This study opens up new possibilities when considering operational problems experienced in in-dustrial gasifiers. Successful completion of this study and a study to look at reducing conditions in the gasifier will also add to the knowledge that already exists regarding fluxing agents.